2022
DOI: 10.1021/acs.cgd.2c00110
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Type I and II Interactions between Halogen Atoms

Abstract: The noncovalent interactions between pairs of halogen (X) atoms on separate molecules are commonly categorized as Type I or II (T1 or T2). T2 contains a standard halogen bond where the two molecules are roughly perpendicular to one another, while the two units in T1 are nearly antiparallel. Quantum calculations reveal that the T2 geometry is more stable than T1 for FX pairs (X = Cl, Br, I) but only by a small amount. In mixed heterodimers FX 1 •••X 2 F, there is a preference for the heavier X atom to serve as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 76 publications
0
22
0
Order By: Relevance
“…This so-called Type II arrangement allows the σ*­(RX) orbital of one unit to best align with one of the lone pairs on the electron-donating X of its partner. An alternative structure, referred to as Type I, is symmetric in the sense that the two θ­(RX···X) angles are roughly equal to one another. This geometry is less stable than Type II, and various reasons have been advanced for this difference over the years. , Recent calculations have shown that Type I represents a transition state for the interconversion of one Type II structure into the other, with the two RX molecules reversing roles as an electron donor or acceptor. The binding of Type I rests on a pair of bent halogen bonds, rather than the single linear XB of Type II.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This so-called Type II arrangement allows the σ*­(RX) orbital of one unit to best align with one of the lone pairs on the electron-donating X of its partner. An alternative structure, referred to as Type I, is symmetric in the sense that the two θ­(RX···X) angles are roughly equal to one another. This geometry is less stable than Type II, and various reasons have been advanced for this difference over the years. , Recent calculations have shown that Type I represents a transition state for the interconversion of one Type II structure into the other, with the two RX molecules reversing roles as an electron donor or acceptor. The binding of Type I rests on a pair of bent halogen bonds, rather than the single linear XB of Type II.…”
Section: Discussionmentioning
confidence: 99%
“…90−92 This geometry is less stable than Type II, and various reasons have been advanced for this difference over the years. 90,93−97 Recent calculations 98 have shown that Type I represents a transition state for the interconversion of one Type II structure into the other, with the two RX molecules reversing roles as an electron donor or acceptor. The binding of Type I rests on a pair of bent halogen bonds, rather than the single linear XB of Type II.…”
Section: The Journal Ofmentioning
confidence: 99%
“…However, there have been numerous examples where the various methods conflict with one another as to which sorts of bonds might be present. [35][36][37][38] There have also been numerous cases described in the literature where AIM locates a bond path where no such bond would appear to exist, or worse, that the interaction in question is a repulsive one. 36,[39][40][41][42][43][44] Another sort of dismaying occurrence is the failure of AIM to identify a bond that is actually present.…”
Section: Introductionmentioning
confidence: 99%
“…It would indeed be comforting for analysis of noncovalent bonds if the methods indicated above provided definitive indicators of the presence of such a bond, and if the data could be treated in a quantitative manner to compare strengths of such bonds. However, there have been numerous examples where the various methods conflict with one another as to which sorts of bonds might be present 35–38 . There have also been numerous cases described in the literature where AIM locates a bond path where no such bond would appear to exist, or worse, that the interaction in question is a repulsive one 36,39–44 .…”
Section: Introductionmentioning
confidence: 99%
“…The nature and strength of halogen⋯halogen interactions strongly depend on their geometry and they are generally classified as either type-I or type-II (Scheme 1ac). 33,34 The type-I is a geometry-based interaction that results from close packing and is common for all halogens (I, Br, Cl, F), whereas type-II results from an electrophile-nucleophile pairing contact stabilized by electrostatic forces, and only type-II interactions are considered to be true XB. However, recent studies have shown that despite the generally accepted rules, halogen bonding can exist between two similarly charged halogen atomic sites (type-III, Scheme 1d).…”
Section: Introductionmentioning
confidence: 99%